2012
DOI: 10.1007/978-3-642-32775-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Open Ecosystems, Collaborative Networks and Service Entities Integrated Modeling Approach

Abstract: This paper introduces an integrated modeling approach that has been used to design and implement the ColNet platform. ColNet is the result of creating an integrated system, supporting distributed business processes design and execution in a Collaborative Network (CN) belonging to an Open Ecosystem (VBE). The work has been carried out as a part of the FP7 REMPLANET European Project, which aims at providing methods and tools for better decision-making in non-hierarchical collaborative networks. The functional al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Romero et al [11] identified a list of processes along the collaboration life cycle, but at a too generic level. Rabelo et al [12], Krogstie [13], Franco et al [14] and Camarinha-Matos et al [15,16] adopted the VBE concept as a wider and logical federation of providers to cope with that wider services-based digital business ecosystems, but also without identifying the required business processes. Cancian et al [17] have elicited the processes and practices for SSPs that want to develop a joint SOA solution, but just assuming that companies would come from a federation.…”
Section: State-of-the-art Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Romero et al [11] identified a list of processes along the collaboration life cycle, but at a too generic level. Rabelo et al [12], Krogstie [13], Franco et al [14] and Camarinha-Matos et al [15,16] adopted the VBE concept as a wider and logical federation of providers to cope with that wider services-based digital business ecosystems, but also without identifying the required business processes. Cancian et al [17] have elicited the processes and practices for SSPs that want to develop a joint SOA solution, but just assuming that companies would come from a federation.…”
Section: State-of-the-art Reviewmentioning
confidence: 98%
“…In order to provide the trust between partners in a Federation some elements should be managed. [14,26,27] Definition of rules, decision making criteria, responsibilities and autonomy levels that should be set up upon the alliance's members, customers and other supporting institutions regarding current contracts and businesses. This process affects all the other ones directly, although with different degrees of intensity Quality management [28] Management of quality aspects upon the alliance's members of their software services and supporting non-software services.…”
Section: Objectivementioning
confidence: 99%
“…Besides there exist several perspectives from which such synergies can be described, to the end of this work, authors have focused on the operational one, paying special attention to the role played by cross-organizational business processes and the performers of tasks as in [4] and [5].…”
Section: Related Conceptsmentioning
confidence: 99%